Initial intracellular proteome profile of Aspergillus Niger biofilms - Villena G.K. (2009)
This work was supported by INCAGRO (Ministry of Agriculture, Perú), CONCYTEC (Ministry of Education, Perú), and the Institute of Molecular Biology and Biotechnology (Shizuoka Univesity, Japan).